Hibiscus Rosasinesis Flower Extract Mediated Ni/ZnO nanoparticles for Visible Light Driven Photocatalytic Degradation of Roseaniline Dye as a Pollutant - Karthiga Rajendaran; Karthikarani Saravanan (Journal of Water and Environmental Nanotechnology)
The green fabricated photocatalyst is promising material and could be applied for waste-water remediation and other ecological applications.Hibiscus floral extract surface modified Ni doped ZnO (HFNZO) was obtained by simple co-precipitation. The flowers have secondary metabolites such as phenolic compounds named as flavonoids; tannins are turned to be the reluctant to synthesize Ni/ZNO nanoparticles from the precursor. The prepared nanoparticles were examined by various characterization for their optical, structural and surface morphology properties was determined using Uv-Drs, FTIR, XRD, SEM, TEM, EDX, and XPStechniques. Absorption spectral shift of visible light region (red shift) and band gap reduction for ZnO (ZO), hibiscus modified ZnO (HFZO) and hibiscus surface modified Ni doped ZnO (HFNZO) properties were studied and shows a reduction in band gap of the nanoparticles from 3.0eV – 1.65 eV. Results obtained from XRD analysis shows that the synthesized HFNZO nanoparticles has a particle size of about 24.85 nm which is also confirmed by TEM analysis. A 98% visible-light-mediated degradation of the aqueous Rose aniline hydrochloride (RA) of 20 µM solution containing HFNZO of 0.05 g/L nanoparticles has achieved within 90 min. It follows pseudo first order Kinetic and the mechanism of generation of hydroxyl group due to flower extract surface modification and doping has been explained.